Dynamic Texture Detection using Flow Estimation based on Texture Constancy - Mançour-Billah, A; H. Ait Laasri, E; Abenaou, A; Agliz, D (International Journal of Computer Sciences and Engineering, 2020)
In this work, we aim to detect and classify different dynamic textures representing scenes of outdoor and indoor environments from video sequences. These scenes constitute the vast majority of events in the world, and their detection offers a wide range of applications. Optical flow is one of the most popular methods for motion estimation due to its efficiency and low computational cost. It is based on the brightness constancy assumption, which assumes a constant brightness of the objects between each two frames over time. However, this assumption is not always verified for dynamic textures with non-uniform surface brightness, due to reflections, shadows, transparency or material diffusion. As an alternative, we propose a new flow estimation method based on texture constancy assumption, which describes the spatial texture components motion. The spatial texture of each point of the image, computed using the LBP operator, is assumed to be constant over time. The resulting flow is called texture flow. From its velocity vectors, we extract the magnitude and orientation, which we combine with the texture spatial features to form a shallow hybrid spatiotemporal descriptor. Experimental results on a benchmark database demonstrate both the ability of our method to distinguish between different types of dynamic textures, and its stability with respect to inter and intra-class differences.